Inappropriate Medication Prescriptions in Elderly Adults Surviving an Intensive Care Unit Hospitalization. Issue 7 (15th July 2013) - Morandi, Alessandro; Vasilevskis, Eduard; Pandharipande, Pratik P.; Girard, Timothy D.; Solberg, Laurence M.; Neal, Erin B.; Koestner, Tyler; Torres, Renee E.; Thompson, Jennifer L.; Shintani, Ayumi K.; Han, Jin H.; Schnelle, John F.; et al.
<x xml:space="preserve">Abstract</x> Objectives To determine types of potentially (PIMs) and actually inappropriate medications (AIMs), which PIMs are most likely to be considered AIMs, and risk factors for PIMs and AIMs at hospital discharge in elderly intensive care unit (ICU) survivors. Design Prospective cohort study. Setting Tertiary care, academic medical center. Participants One hundred twenty individuals aged 60 and older who survived an ICU hospitalization. Measurements Potentially inappropriate medications were defined according to published criteria; a multidisciplinary panel adjudicated AIMs. Medications from before admission, ward admission, ICU admission, ICU discharge, and hospital discharge were abstracted. Poisson regression was used to examine independent risk factors for hospital discharge PIMs and AIMs. Results Of 250 PIMs prescribed at discharge, the most common were opioids (28%), anticholinergics (24%), antidepressants (12%), and drugs causing orthostasis (8%). The three most common AIMs were anticholinergics (37%), nonbenzodiazepine hypnotics (14%), and opioids (12%). Overall, 36% of discharge PIMs were classified as AIMs, but the percentage varied according to drug type. Whereas only 16% of opioids, 23% of antidepressants, and 10% of drugs causing orthostasis were classified as AIMs, 55% of anticholinergics, 71% of atypical antipyschotics, 67% of nonbenzodiazepine hypnotics and benzodiazepines, and 100% of muscle relaxants were deemed AIMs. The majority of PIMs and AIMs were first prescribed in the ICU. Preadmission PIMs, discharge to somewhere other than home, and discharge from a surgical service predicted number of discharge PIMs, but none of the factors predicted AIMs at discharge. Conclusion Certain types of PIMs, which are commonly initiated in the ICU, are more frequently considered inappropriate upon clinical review. Efforts to reduce AIMs in elderly ICU survivors should target these specific classes of medications.